PROCEEDING : RISK REDUCTION STRATEGY BY USING RAIN SHELTER ON CHILI PEPPER AGRIBUSINESS - Sri Ayu Andayani (REPOSITORY BUKU DAN JURNAL)
The plenty of red Chili demand pull up farmers to continue production of red chili and adjust it with industrydemand specification. The supply of red chili will be guaranteed if the production is going well. In fact, theproduction process frequently faces the climate disturbance therefore it was indicated that there is a risk inproduction, it deteriorated quality and quantity of red chili. Garut regency is one of the center of production ofred chili in West Java, but it is still threatened by risk production. According to that information, it is needed tostudy the elements and link period pattern of risk production then it can be suggested the policy design inmitigating the risk production. This study used dynamic system approach. The results showed that riskproduction occured when there was a death structure in growingand production period which is caused by climateanomaly. The simulation result showed that us period of technology rain shelter as one suggested design tomitigate the risk, not only can reduce the mortality but also to promote the grade product quality.Keywords : red chili. Production risk, mitigation